Perceived psychological distress and learning barriers on emergency remote education: association with students’ motivation and resilience - Shyra Grace Bauya; Mary Princess Cacayan; Diane Mae Ulanday (Journal of Science and Education)
Emergency remote education has become a critical learning platform that created changes in ways of attaining learning goals. This shift to a new learning platform posed a great challenge to students’ motivation and resilience in learning. This study aimed to analyze the students' learning barriers and psychological distress and their motivation and resilience in studying during the public health emergency. A descriptive-correlational research design was utilized to assess the research questions posed in this study. The respondents of the study were the two hundred thirty- eight (238) BEED students of Mindanao State University, General Santos City who were officially enrolled during the S.Y. 2021-2022. The researchers employed a stratified sampling technique in selecting the respondents for this study. Adapted questionnaires such as the Depression, Anxiety, Stress Scale-21 (DASS-21), Learning Barriers Questionnaire, Motivation to Learn Online Questionnaire (MLOQ), and the Connor-Davidson Resilience Scale (CD-RISC), checked and validated by experts, were used to gather the needed data. Descriptive statistics and Pearson Product Moment- Correlation Coefficient were used to analyze and interpret the gathered data. In this study, the researchers found that psychological distress significantly influences the resilience of students, but it does not influence their motivation to learn. Results also revealed that the learning barriers significantly influence both motivation and resilience of the students. Replication of this study is highly recommended using qualitative research design and including other variables such as assessments and the engagements of students.